Flatliners (1990) [videorecording (DVD)] - Schumacher, Joel, 1939-2020-; Sutherland, Kiefer, 1966-; Roberts, Julia, 1967-; Bacon, Kevin, 1958-; Baldwin, William, 1963- (Mill Creek Entertainment, 2014)
An ambitious, charismatic medical student persuades two classmates to take part in an experiment to determine if there is life after death. Their horror begins when they realize that although they've come back alive, they haven't come back alone.